PENGEMBANGAN MODUL DENGAN MENGGUNAKAN PENDEKATAN SAINTIFIK PADA KELAS X SEKOLAH MENENGAH ATAS - Rio Septora (Lembaga Penelitian UM Metro, 2017)
This study aims to develop a product of effective teaching materials for use by students of class X High School, Teaching materials developed are modular teaching materials. This research uses research and development method by adapting model development of Banathy and Dick model, Carey and Carey. To obtain information on the feasibility of teaching materials, expert validation and limited field testing are performed. Validation is done to the feasibility of curriculum (material and content), language, and grafic (presentation) by using questionnaire scale 5 by lecturer Data in limited field test obtained through multiple choice test. Subjects in a limited field trial comprised 35 students. Based on the analysis of expert validation results, module development can be categorized as good or feasible. The results of a text knowledge test show an average increase in the value of multiple choice tests changed from 75.71 to 85.14 with a margin of 9.43. In the test the ability to understand the structure and rules of text shows the average of 70.46 to 85.2 (difference 14.74). Thus, this development result module can improve students' ability to understand text and provide potential effects.